2012
DOI: 10.1074/jbc.m111.324350
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Envelope Phosphatase 1-Regulatory Subunit 1 (Formerly TMEM188) Is the Metazoan Spo7p Ortholog and Functions in the Lipin Activation Pathway

Abstract: Background: Lipins are phosphatidic acid phosphatases. In yeast, lipin is activated by the Nem1p-Spo7p complex. There is controversy as to whether a mammalian Spo7p ortholog exists. Results: The metazoan Spo7p ortholog is now identified and shown to interact with lipins in yeast, nematodes, and mammalian cells. Conclusion: NEP1-R1 is the metazoan Spo7p ortholog. Significance: The lipin activation system is conserved in evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
131
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(143 citation statements)
references
References 65 publications
7
131
0
Order By: Relevance
“…Inhibition of the C. elegans homolog of the lipin activator CTDNEP1, called CNEP-1, slows nuclear envelope disassembly during the first division of the C. elegans embryo (Han et al 2012), a phenotype also observed following partial inhibition of lipin (LPIN-1 in C. elegans) (Golden et al 2009;Gorjá ná cz and Mattaj 2009;Han et al 2012). To investigate how CNEP-1 promotes nuclear envelope disassembly, we generated transgenes expressing GFP fusions with lipin and wild-type or phosphatasedefective (PD) CNEP-1 (CNEP-1 WT or CNEP-1 PD ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of the C. elegans homolog of the lipin activator CTDNEP1, called CNEP-1, slows nuclear envelope disassembly during the first division of the C. elegans embryo (Han et al 2012), a phenotype also observed following partial inhibition of lipin (LPIN-1 in C. elegans) (Golden et al 2009;Gorjá ná cz and Mattaj 2009;Han et al 2012). To investigate how CNEP-1 promotes nuclear envelope disassembly, we generated transgenes expressing GFP fusions with lipin and wild-type or phosphatasedefective (PD) CNEP-1 (CNEP-1 WT or CNEP-1 PD ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lipin activity and localization are regulated via multisite phosphorylation by Cdk1 and mTORC1 (Carman and Han 2011;Siniossoglou 2013), which negatively regulate lipin activity (Eaton et al 2013). The conserved C-terminal domain (CTD) phosphatase CTDNEP1 (formerly Dullard) is an integral membrane protein enriched on the nuclear envelope that is predicted to activate lipin by dephosphorylating it (Siniossoglou et al 1998;Kim et al 2007;Han et al 2012;Eaton et al 2013).Lipin inhibition in HeLa cells and Caenorhabditis elegans embryos slows nuclear envelope disassembly during mitosis (Golden et al 2009; Gorjá ná cz and Mattaj 2009;Mall et al 2012). This has been proposed to result from a reduction in DAG levels, which in turn could decrease the activity of DAG-dependent protein kinase Cs that phosphorylate lamins to promote their disassembly (Mall et al 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lipin-1 is the best characterized member of the mammalian family, followed by lipin-2. Lipins are predominantly cytosolic proteins that translocate to their sites of action in the endoplasmic reticulum and nucleus (5)(6)(7)(8)(9)(10)(11)(12)(13). These changes are dictated by a polybasic nuclear localization motif (6,9,14), which also promotes an electrostatic interaction with negatively charged phosphatidate, fatty acids, and acyl-CoA esters on the membrane surface (9, 14 -17).…”
mentioning
confidence: 99%
“…Conversely, positively charged amphiphilic compounds, such as chlorpromazine and sphingosine, reverse this translocation (16,18). Importantly, increasing the negative charge on the lipins through phosphorylation decreases their interactions with negative charges on the surfaces of membranes to control subcellular distribution and function (5,6,10,19). This is demonstrated by the cytosolic localization of hyperphosphorylated forms of lipins, whereas hypophosphorylated lipins translocate to the nucleus and endoplasmic reticulum (5,6,11,19).…”
mentioning
confidence: 99%